Plastics Biodegradation in the Short Term in a Mediterranean Soil and the Effect of Organic Amendment - Rafael Boluda; Nadia Redondo; Luis Roca-Pérez; Eva Fernández-Gómez; Oscar Andreu-Sánchez (Toxics, 2025)
The main problem with the conventional plastics presently used is that they are too slow to degrade, and thus, accumulate in the natural environment. This situation occurs on farmlands because low-density polyethylene (LDPE) is widely used in agriculture. Different authors propose employing biodegradable plastics (bioplastics) to solve this problem, and the most studied and promising candidates are poly(hydroxybutyrate) acid (PHB) and poly(lactic) acid (PLA). This work centers on the short-term evaluation of the biodegradability of the three above-mentioned plastic materials in soil type Mediterranean Alfisol and the effect of adding organic amendment (cow manure; CM) on their biodegradation. Two experiments were run for each plastic material: one without this organic amendment and the other by adding CM. Their biodegradation was determined by the procedure described in Standard ISO 17556. The results confirm that PHB is a highly biodegradable polymer, whereas the biodegradability of PLA and LDPE is poor. Using CM did not facilitate plastic polymer biodegradation in our soil. The nature and properties of soil can significantly impact plastics biodegradation. Bioplastics are still not the panacea to solve the plastics pollution problem, so other management options must be considered, such as prevention, reduction, and/or reuse in situ.